Knowledge and presuppositions - Blome-Tillmann, Michael (Oxford University Press, 2014)
Michael Blome-Tillmann presents an innovative account of epistemic contextualism, based on the idea that pragmatic presuppositions play a central role in the semantics of knowledge attributions. He shows how the theory can resolve sceptical paradoxes and puzzles, and illuminate concerns central to epistemology and philosophy of language
Keywords: Epistemics; Presupposition (Logic); Contextualism (Philosophy); Annahme; Erkenntnistheorie; Kontextualismus